CRITICAL LISTENING IN HIGHER EDUCATION: INSIGHTS FROM INDONESIAN EFL LEARNERS - Gunawan, Aninda Putri; Gustine, Gin Gin; Gunawan, Muhammad Handi (University of Kuningan, 2023)
This research aims to examine the practice of critical listening in higher education. This investigation involves fourth-semester students in the English Education Department of an Indonesian public state institution. This research utilized a qualitative case study. This study's data were collected using a triangulation method incorporating classroom observation, questionnaires, and semi-structured interviews. In this research, the data were analyzed thematically. According to the data analysis, students benefited from implementing critical listening in the classroom because the critical listening practice focused on essential listening competencies, helped them develop critical thinking, and promoted critical listening in the classroom. Students believed that critical listening aids in developing their language skills and allows them to exercise critical thinking skills that have yet to be covered in class. The findings of this study can provide educators with a starting point for implementing critical listening with EFL students. In other words, the findings may cast light on implementing critical listening, including the general benefits and challenges students encounter.